2015
DOI: 10.4103/0301-4738.159861
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of choroidal imaging technologies

Abstract: Choroid supplies the major blood supply to the eye, especially the outer retinal structures. Its understanding has significantly improved with the advent of advanced imaging modalities such as enhanced depth imaging technique and the newer swept source optical coherence tomography. Recent literature reports the findings of choroidal changes, quantitative as well as qualitative, in various chorioretinal disorders. This review article describes applications of choroidal imaging in the management of common diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…Recently, OCT has been shown to provide advanced imaging to evaluate the three-dimensional anatomy of the choroid layers and retinal pigment epithelium. 10,11 In studies using OCT, the choroidal thickness has been reported to be decreased in patients with diabetic retinopathy, rheumatoid arthritis, and myopia. [12][13][14] Xin et al 15 reported that the choroidal thickness was thinner in patients with obstructive sleep apnea syndrome due to intermittent hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, OCT has been shown to provide advanced imaging to evaluate the three-dimensional anatomy of the choroid layers and retinal pigment epithelium. 10,11 In studies using OCT, the choroidal thickness has been reported to be decreased in patients with diabetic retinopathy, rheumatoid arthritis, and myopia. [12][13][14] Xin et al 15 reported that the choroidal thickness was thinner in patients with obstructive sleep apnea syndrome due to intermittent hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Fluorescein angiography (FA) and indocyanine green angiography (ICGA), visualizing the retinal and choroidal vasculature, may play a significant role in the assessment of vascular changes and choroidal infiltrations. 12,14 Furthermore, enhanced depth imaging (EDI) optical coherence tomography (OCT) may provide additional useful information on retinal and choroidal structures. 14 The present study aims to prospectively analyze, using a multimodal imaging approach, the subclinical intraocular involvement in patients affected by ECD without ocular symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…12,14 Furthermore, enhanced depth imaging (EDI) optical coherence tomography (OCT) may provide additional useful information on retinal and choroidal structures. 14 The present study aims to prospectively analyze, using a multimodal imaging approach, the subclinical intraocular involvement in patients affected by ECD without ocular symptoms. This topic is of paramount relevance to assessing whether ECD patients should undergo periodic ophthalmic examinations.…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of the choroid in myopes is reduced compared to subjects without this refractive error [ 4 ] and at the same time correlates significantly with the axial length [ 5 , 6 ]. In myopia, photoreceptors and choriocapillaris are rarefied, and the retinal pigment epithelium is diffusely depigmented [ 7 ]. In the retina, the density of the superficial and deep vascular network is reduced [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%